The Greek family in Cape Town - Added, Emile Lucien (Social Anthropology, 2015)
The aim of this study is to establish what influence the impact of the new environment has on the structure of the Greek family in Cape Town, the impact on the functions which the family fulfils in the socialisation of the children, and on the family's social influence on the intergenerational relationship. The study will focus on the Greeks of rural origin, as most of the Greeks in Cape Town come from a rural background. Various anthropological studies on the Greek peasant emphasise the centrality of the Greek family in the life of the individuum.